P-370 The vaginal microbiome in the first trimester of pregnancy is different in spontaneous versus IVF gestation. (30th June 2022) - Fuentes, A; Lledo, B; Lozano, P; Cascales, A; Morales, R; Hortal, M; Palacios-Marqués, A; Bermejo, R; Quereda, F; Escoriza, J.C. Martínez; Bernabeu, R; Bernabeu, A
Abstract: Study question: Are there differences in the vaginal microbiome of pregnant women who had a spontaneous pregnancy compared to those who required IVF? Summary answer: The composition of the vaginal microbiome at 12 week's gestation is different in women who achieve the pregnancy spontaneously or by IVF. What is known already: The vaginal microbiome plays an important role in women's reproductive health, finding associations between different microbiome patterns and the presence of infertility and embryo implantation failure in IVF. Additionally, recent studies show a correlation between obstetrics and perinatal outcomes and the composition of vaginal microbiota in pregnant women, as well as an increased risk of obstetrics complications in pregnant women after IVF. Study design, size, duration: Observational, prospective and multicentre study. A total of 64 women were enrolled between January 2020 and June 2021. Spontaneous pregnancies n = 30; and IVF pregnancies n = 34. Participants/materials, setting, methods: Vaginal swabs were obtained by speculum exam at 12 weeks of gestation in two public hospitals and a fertility private clinic in Spain, to evaluate the differences in vaginal microbiome between both cohorts. The microbiome composition was analyzed by sequencing the V3-V4 region of the 16S rRNA on the Illumina MiSeq platform. Main results and the role of chance: There were no significant differences in socio-demographic characteristics between groups, except for an expected higher maternal age in the IVF cohort. Lactobacillus was the most prevalent genus in both groups. When we compared the beta diversity of vaginal microbial by cohort a significant difference was obtained (p = 0.001). Gardenella, Neisseria, Prevotella and Staphyloccocus were significantly enriched in the IVF group (p = 0.01). A further evaluation of the four most abundant Lactobacillus species showed that Lactobacillus iners was dominant in IVF pregnancies (15.2%) compared to spontaneous (9.8%) (p = 0.002). On the other hand, Lactobacillus   gasseri showed a lower abundance in vaginal microbiome from women belonged to IVF (9.2%) vs spontaneous pregnant group (13.8%) (p = 0.005). These findings allowed us to create a model to identify a microbial signature. This model is able to discriminate between IVF and spontaneous pregnancies. Limitations, reasons for caution: The main limitation of our study is the small sample size. Larger studies are needed to corroborate our findings and their relationship with important aspects such as obstetric and perinatal complications. Wider implications of the findings: The microbiome composition is different between both cohorts. The microbiome found in our IVF cohort has been also associated with obstetric complications as preterm delivery in previous studies. This suggest that the microbiome composition could be a plausible etiology for a higher risk of adverse pregnancy outcomes in IVF patients. Trial registration number: Not applicable